Design, development, and biopharmaceutical properties of Buccoadhesive compacts of pentazocine - Agarwal V.; Mishra B. (My University, 2025)
Buccoadhesive compacts (BCs) of pentazocine (PZ) were prepared by the direct compression method using polymers like carbopol 974P (CP 974P) and hydroxypropyl methylcellulose (HPMC K4M) in ratios of 1:0 (batch B1), 1:1 (B2), 1:2 (B3), 1:4 (B4), and 0:1 (B5). The compacts were evaluated for thickness uniformity, weight variation, drug content uniformity, and swelling index. Swelling was increased with an increase in HMPC K4M content in the compacts. An in vitro assembly was developed to measure and compare the bioadhesive strength of compacts. The maximum bioadhesive strength was observed in compacts formulated with a combination of CP 974P and HPMC K4M. The compacts were evaluated in vitro for 24 hr in pH 6.6 phosphate buffer using a standardized dissolution apparatus. The data were evaluated by a simple power equation (M(t)/M(∞) = Kt(n)); it was observed that all the compacts followed non-Fickian release kinetics. Some of the buccoadhesive compacts were evaluated in vivo in rabbits. The compacts gave controlled blood level profiles with a twofold to threefold increase in area-under-the- curve (AUC) values in comparison to oral administration of aqueous drug solution.